2017
DOI: 10.1177/2050640616675219
|View full text |Cite
|
Sign up to set email alerts
|

Capsule retention related to small bowel capsule endoscopy: a large European single‐center 10‐year clinical experience

Abstract: This large clinical material demonstrates that CR is a rare complication with a favorable clinical outcome. Most patients with CR can be electively managed with non-surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 45 publications
5
49
0
1
Order By: Relevance
“…The detection rate was 64.5%, and there was no capsule retention. This study showed values of the detection rate, completion rate and retention rate (64.5%, 77.4%, and 0%, respectively) that were comparable to those in previously published data with conventional capsule endoscopy (60-63%, 80-83%, and 1-2%, respectively) [18][19][20][21][22] . Even though the function of 3D reconstruction and size estimation was fascinating, these functions did not contribute significantly to the clinical management of most patients in this study.…”
Section: Discussionsupporting
confidence: 89%
“…The detection rate was 64.5%, and there was no capsule retention. This study showed values of the detection rate, completion rate and retention rate (64.5%, 77.4%, and 0%, respectively) that were comparable to those in previously published data with conventional capsule endoscopy (60-63%, 80-83%, and 1-2%, respectively) [18][19][20][21][22] . Even though the function of 3D reconstruction and size estimation was fascinating, these functions did not contribute significantly to the clinical management of most patients in this study.…”
Section: Discussionsupporting
confidence: 89%
“…VCE is a safe technique and accumulating data from large studies indicate that the incidence of intestinal retention is less than 2%. Certain conditions, such as intestinal tumours and Crohn's disease that limit passage in the small bowels may predispose capsule retention in the GI tract potentially causing bowel obstruction (9,10). The most common site of capsule retention is the small bowel, but other localizations, including oesophagus, stomach and airways have also been reported (12).…”
Section: Discussionmentioning
confidence: 99%
“…Beside the work-up of obscure gastrointestinal bleeding (OGIB) and in the evaluation of intestinal lesions related to non-steroidal anti-inflammatory drugs (NSAIDs) and celiac disease, VCE is particularly useful in the diagnosis and surveillance of Crohn's disease (3)(4)(5)(6)(7)(8). It is generally held that VCE is a safe method to examine the small bowel (9,10). Nonetheless, capsule retention is a feared complication with the potential to cause acute small bowel obstruction requiring emergency surgery (11).…”
Section: Introductionmentioning
confidence: 99%
“…Retencija se definira kao prisutnost kapsule u crijevu 14 dana nakon ingestije s incidencijom od 1 do 2% pri suspektnom CB-u, dok kod dokazanog CB-a raste do 13%. 6 Znatno suženje lumena crijeva zbog tumora ili striktura povisuje rizik od retencije. Retinirana se endokapsula uklanja enteroskopijom, a nemogućnost izvlačenja odnosno nenalaženje endokapsule nalaže njezino kirurško uklanjanje.…”
Section: Raspravaunclassified